Intelligent Decoupling Control Study of PMSM Based on the Neural Network Inverse System - Da-Wei, Gong; Zhi-Qiang, Qiu; Wei, Zheng; Zhi-Wu, Ke; Yang, Liu (Frontiers in Energy Research, 2022)
This paper obtains the analytical inverse system of PMSM model based on the traditional magnetic field orientation decoupling control mode by analyzing inverse quality of PMSM. Using the neural network’s excellent approximation ability and well learning function, neural network inverse system decoupling control system was established by identifying and offline training BP and RBF neural network. The data collected from analytical inverse system of PMSM model. Through the comparison and analysis of the prediction precision and running time of the neural network, the structure and parameters are optimized. Three kinds of PMSM decoupling control system simulation show that the decoupling control system of PMSM based on RBF neural network inverse system has more good dynamic and static decoupling performance and robustness.